Summary of Proprioceptive Training on Motor Dysfunction Rehabilitation - Renxin JI; Wenhua CHEN; Qi QI (康复学报)
Summary of the effectiveness of different types of proprioception training on motor dysfunction caused by different diseases by analyzing a number of relevant literatures at home and abroad. Findings showed that motor dysfunction was the most common symptom in stroke, sports injury, musculoskeletal disease, lumbar vertebrae degeneration, dystonia, etc.. A large number of reports advocated that the above diseases all had the loss of proprioception. It was necessary to apply proprioceptive training. Proprioceptive training included active movement and balance training, passive movement training, somatosensory stimulation training, somatosensory discrimination training and multiple system training. Somatosensory stimulation training was effective in patients with motor dysfunction caused by central nerve injury. Passive movement training and balance training could effectively improve motor function of patients with sports injury; otherwise, the total effective rate of active movement training was relatively low. Whole body vibration of somatosensory stimulation training was the most effective form to improve motor dysfunction caused by dystonia in patients with Parkinson's disease. Proprioception training had got more and more attention on rehabilitation of patients with a variety of motor dysfunction.